Low-risk triple-negative breast cancers: Clinico-pathological and molecular features. (April 2022) - Fusco, Nicola; Sajjadi, Elham; Venetis, Konstantinos; Ivanova, Mariia; Andaloro, Silvia; Guerini-Rocco, Elena; Montagna, Emilia; Caldarella, Pietro; Veronesi, Paolo; Colleoni, Marco; Viale, Giuseppe
Abstract: Triple-negative breast cancers (TNBC) comprise biologically and clinically heterogeneous diseases characterized by the lack of hormone receptors (HR) and HER2 expression. This subset of tumors accounts for 15–20% of all breast cancers and pursues an ominous clinical course. However, there is a spectrum of low-risk TNBCs with no/minimal metastatic potential, including the salivary gland-type tumors, those with extensive apocrine differentiation and/or high tumor-infiltrating lymphocytes, and small-sized, early-stage (pT1a/bN0M0) TNBCs. De-escalating the treatment in low-risk TNBC, however, is not trivial because of the substantial lack of dedicated randomized clinical trials and cancer registries. The development of new diagnostic and/or prognostic biomarkers based on clinical and molecular aspects of low-risk TNBCs would lead to improved clinical treatment. Here, we sought to provide a portrait of the clinicopathological and molecular features of low-risk TNBC, with a focus on the diagnostic challenges along with the most important biological characteristics underpinning their favorable clinical course. Graphical Abstract: ga1 Highlights: Triple-negative breast cancers (TNBC) are commonly related to poor prognosis. There is a spectrum of low-risk TNBCs with no/minimal metastatic potential. Low-risk TNBC group shows a low frequency of genomic instability and indolent clinical course. Comprehensive studies and clinical trials on low-risk TNBC patients are still lacking. Detailed molecular characterization of low-risk TNBC may lead to tailored clinical management.